PENGEMBANGAN KEGIATAN EKONOMI SEBAGAI UPAYA ADAPTASI PERUBAHAN LINGKUNGAN FISIK PERAIRAN LAGUNA SEGARA ANAKAN - Edyanto, CB Herman (Jurnal Hidrosfir Indonesia, 2009)
Sedimentation is a natural process which is materialized in the river. It is made happen by the erosion processes and also often because of illegal logging in upstream . Segara Anakan is situated in central Java and is one of the largest lagoon in the world which experiences sedimentation year by year and at present the rest of the watery lagoon is not more than 600 ha. The environment has been being changed. Some of water area conversed to be the land naturally, and it is predicted that the specific biota like eel fish will be vanished. The lagoon cannot be protected anymore from the natural sedimentation processes. Adaptation to this change should, therefore, be made to convert the status quo land - called as land colmatation - to be the more economic activities for the people.